Evaluation of two methods for counting residual leukocytes in leukoreduced packed red cells: Flow cytometry and fully automated cell counter - Mamta Shah; Nidhi Bhatnagar; Sangita Shah; Falguni Pandav; Hetali Shah; Anupa Dixit; Trupti Shetty; Pushkar Admane; Ankur Lath; Prakash Suvasia (Asian Journal of Transfusion Science)
BACKGROUND AND OBJECTIVES: Objective of the study is to explore the possibility of utilization of seven part fully automated hematology analyzer for enumeration of residual leukocytes (residual white blood cells [rWBCs]) in leukoreduced packed red cells (LR-PRCs) prepared from whole blood at a blood center as an alternate to the gold standard method, flow cytometry. In this study, we evaluate the performance characteristic of hematology analyzer against flow cytometry for the estimation of rWBCs in 39 LR-PRC units. MATERIALS AND METHODS: PRCs prepared from whole blood donations by 39 donors were leukoreduced and their volumes were noted. The samples from these LR-PRCs were processed on HORIBA Yumizen H2500 hematology analyzer and Backman Coulter DxFlex (B5R3V5) Flow Cytometer and compared. RESULTS: A total of 39 LR-PRCs were analyzed. The average volume of these LR-PRC units was 252 mL ranging from 227 to 285 mL/bag. The average rWBC count for all LR-PRC units as per flowcytometry method was 3.1 × 106/bag. There were 5 LR-PRC units with rWBC count more than 5 × 106/bag which did not fulfill the minimum quality control criteria of LR-PRCs as per the Indian standards (DGHS). CONCLUSION: The new generation fully automated hematology analyzers could be simple, reliable, economical, and practically best method for assessing the efficacy of leukoreduction in LR-PRCs. They can be adopted by resource-constrained blood centers as an alternative to flow cytometry for this purpose. It can be practically applied to check the quality of leukoreduction in all blood component samples before release from blood center for transfusion to the patients.